Emergence and Autochthonous Transmission of Dengue Virus Type I in a Low-Epidemic Region in Southeast China - Zhang, Yi; Chen, Hongyi; Wang, Jingen; Wang, Shumei; Wu, Jing; Zhou, Yang; Wang, Xinyu; Luo, Feibing; Tu, Xianglin; Chen, Qiubo; Huang, Yanxia; Ju, Weihua; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background. Dengue fever is a mosquito-borne febrile illness. Southeast Asia experienced severe dengue outbreaks in 2019, and over 1000 cases had been reported in Jiangxi, a previously known low-epidemic region in China. The emergence of a dengue virus epidemic in a non-epidemic region remains unclear. Methods. We enrolled 154 dengue fever patients from four hospitals in Jiangxi, from April 2019 to September 2019. Real-time PCR, NS1 antigen rapid test, and IgM, IgG tests were performed, and 14 samples were outsourced to be sequenced metagenomically. Results. Among the 154 cases, 42 were identified as imported and most of them returned from Cambodia. A total of 113 blood samples were obtained and 106 were identified as DENV-1, two as DENV-2, and five were negative through RT-PCR. All DENV-1 strains sequenced in this study were all classified to one cluster and owned a high similarity with a Cambodia strain isolated in 2019. The evolutionary relationships of amino acid are consistent with that of nucleotide genome result. The sequence-based findings of Jiangxi strains were consistent with epidemiological investigation. Conclusion. Epidemiological analysis demonstrated that the emergence of dengue cases led to autochthonous transmission in several cities in Jiangxi, a low-epidemic region before. This study emphasized future prevention and control of dengue fever in both epidemic and non-epidemic regions.